1983
DOI: 10.1038/bjc.1983.247
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-emetic efficacy and toxicity of nabilone, a synthetic cannabinoid, in lung cancer chemotherapy

Abstract: Nabilone is an effective oral anti-emetic drug for moderately toxic chemotherapy, but the range and unpredictability of its side-effects warrant caution in its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 11 publications
1
44
0
1
Order By: Relevance
“…35 36 58-60 In nine trials, all patients were reported not to have used cannabis previously. 33 34 39 41-43 46 49 51 In the other 16 trials, it was unclear whether patients had used cannabis previously.…”
Section: Resultsmentioning
confidence: 99%
“…35 36 58-60 In nine trials, all patients were reported not to have used cannabis previously. 33 34 39 41-43 46 49 51 In the other 16 trials, it was unclear whether patients had used cannabis previously.…”
Section: Resultsmentioning
confidence: 99%
“…It binds to cannabinoid receptors like D 9 -THC but was found to be without psychoactive properties [5,6]. It is the only legally available cannabinoid preparation in the United Kingdom and is licensed solely for use in reduction of nausea and vomiting induced by chemotherapy [7,8].…”
mentioning
confidence: 99%
“…Die orale Applikation von Nabilone wurde in 16 Studien untersucht [1,5,6,7,10,12,14,17,20,25,26,28,38], Dronabinol in 13 Studien [3,4,11,13,18,19,23,24,27,31,32,41] und die intramuskuläre Gabe von Levonantradol in einer Studie [16]. In diesen Studien wurden Cannabinoide nach 1-6 Chemotherapiezyklen eingesetzt und die antiemetische Effektivität über 24 h untersucht.…”
Section: Nabilone Dronabinol Und Levonantradolunclassified